The new Westminster dictionary of Christian spirituality - Sheldrake, Philip (Louisville, Ky. : Westminster John Knox Press, 2005)
This new volume, replacing The Westminster Dictionary of Spirituality by Gordon S. Wakefield (1983), stands as the definitive reference work on all aspects of Christian spirituality. Several years in the making and comprised of more than 400 completely new entries, the Dictionary incorporates the collective expertise of today's foremost scholars in the field of Christian spirituality. Systematically organized and alphabetically arranged for maximum ease of use, the book includes comprehensive bibliographies; a section of short essays on the content, methods, and current debates in the field; and reading lists to encourage additional reading and research. Philip F. Sheldrake is Professor in the Department of Theology and Religion, University of Durham.
Essays. Christian spirituality : definition, methods, and types / Sandra C. Schneiders -- Contemporary spirituality / Valerie Lesniak -- Interpretation / Philip Sheldrake -- Mysticism / Bernard McGinn -- Spirituality and culture / James Corkery -- Spirituality and the dialogue of religions / Michael Barnes -- Spirituality and history / Philip Sheldrake -- Spirituality, liturgy, and worship / Susan J. White -- Spirituality, psychology and psychotherapy / John Shea -- Spirituality and science / Robert John Russell -- Spirituality and scripture / Sandra M. Schneiders -- Spirituality and social sciences / Claire E. Wolfteich -- Spirituality and theology / Philip Endean -- Entries A-Z.
"First published in Great Britain in 2005 under the title The new SCM dictionary of Christian spirituality."--T.p. verso.
Includes bibliographical references and index.
Keywords: Spirituality -- Dictionaries